مقارنة بعض المؤشرات الانثروبومتریة ونتائج الاختبارات البدنیة بین الطلاب المقبولین والغیر مقبولین في كلیة التربیة الریاضیة الجامعة المستنصریة - عثمان فخرالدين محمود (physical education and sport sciences college for women/ Baghdad University, 2014)
The aim of this study is to identify the difference for Anthropometric variety and physical test result between acceptance and non acceptance student. The researcher assumed that there was no significant differences between the anthropometric variety and physical test results. The researcher used comparative curriculum. The results shows that run 60 (2.60), run 540 (2.51), long jump (3.30), exercise belly (2.36), and push up (1.94) better than table value (1.64). While there was no BM (0.52), BT (0.06). but it was sigmficart difference in FM (8.82). The conclusion of the results include force and weak the difference between the tests. The results show that (BF) for non acceptance students was better and significant than acceptance students. While both (BM, BT) for acceptance students was better and significant than non acceptance students. It is important to do similar studies for the same study variety of the physical test used between acceptance and non acceptance for colleges of physical education in Iraq both at male and female